Kolkhoz Members in the Ukraine - Jeremy Younkin:::Creator::::::::::::
Color photo of the members of the Kolkhoz at Shevshenko. Steinbeck and Capa most likely visited this Kolkhoz. Here, older members are questioned by Ira (a companion of the photographer) about whether they remembered Steinbeck or Capa having visited. None of them did, but other details matched descriptions in the book.